Acceptance of E-Government by Civil Servants in Siak Regency Using the Technology Acceptance Model Approach - Dita Fisdian Adni; Khairul Rahman; Syaprianto; Suzan Olivia (Indonesian Journal Publisher, 2026)
This study aims to analyze the acceptance of e-government by the State Civil Apparatus (ASN) in Siak Regency through the implementation of E-Absensi using the Technology Acceptance Model (TAM) approach, specifically in understanding the perception of usefulness (Perceived Usefulness), ease of use (Perceived Ease of Use), and Attitude and Intention of Use (Attitude & Behavioral Intention). The method is a qualitative approach using interviews, observation, and documentation, with data analysis in NVivo 12 Plus and triangulation techniques to ensure the validity and reliability of the findings. The findings of this study indicate that acceptance of e-government through the implementation of E-Absensi by ASN in Siak Regency has been ongoing but remains in a transitional stage between administrative compliance and substantive adoption. The perception of usefulness (Perceived Usefulness) is strong, as ASN recognizes that E-Absensi can improve discipline, transparency, and work efficiency. However, the perception of ease of use (Perceived Ease of Use) still faces several obstacles, including limited system access, differences in digital literacy, and technical barriers that affect the user experience. As a result, attitudes and behavioral intentions are driven more by policy pressures and organizational obligations than by intrinsic awareness.